Kesiapan Memasuki Sekolah Dasar pada Anak yang Mengikuti Pendidikan TK dengan yang Tidak Mengikuti Pendidikan TK di Kabupaten Kudus - Halimah, Nur; Kawuryan, Fajar (Jurnal Psikologi: PITUTUR, 2010)
This present study is aimed to investigate the  school  readiness  differences  between student who took pre-scholl education and not took pre-school education. Participants of this study consist of 120 students in the first class of elementary  shool  from  different  school  in Kudus.  This  study  use  accidental  sampling. NST  (Nijmeegse  Schoolbekwaamheids  Test) that made by Monks, Rost, and Coffie are used to know the school readiness. t analyses were performed and get the difference coeficient t1.2 =53,405,  p=0,000 (p<0,01). This result showed that  there  are  very  significant  differences school  readiness  between  student  who  took pre-shcool education and not took pre-school education.  The  student  who  took  pre-school education  have  better  school  readiness  if compare with student who not took pre-school education. This is showed by mean difference from  two  kind  of  the  participant.  The  student who took pre-school education get the mean score 25,98 but the student who not took pre-school education only get mean score 11,25.